Hak Cipta Musik Dan Pengaruhnya Terhadap Industri Musik Di Indonesia - Marsela Berliana; Silalahi, Wilma (USRAH: Jurnal Hukum Keluarga Islam, 2025)
Copyright protection of musical works plays a crucial role in ensuring the sustainability and growth of the music industry in Indonesia. This study aims to examine the legal provisions of music copyright as stipulated in Law Number 28 of 2014, and to analyze its influence on the dynamics of the national music industry. Using a normative juridical approach, this research explores various issues such as rampant piracy, weak law enforcement, and the complexity of royalty management. The findings reveal that despite the existence of legal frameworks, implementation remains suboptimal due to low legal awareness, limited resources, and the challenges posed by rapid digital technological developments. Strategic measures are therefore necessary, including regulatory reform, public education, and strengthened stakeholder collaboration. In doing so, copyright protection will not only ensure justice for creators but also reinforce the overall ecosystem of the Indonesian music industry.